External Innovation in Javanese Vocabulary of Banten Dialect (A Study of Dialect Geography) - Tatu Siti Rohbiah; Uyu Mu’awwanah (Scope : Journal of English Language Teaching, 2023)
This research is aimed to describe and to explain external innovation in the variant categories of word classes found in the usage of Banten dialect of Javanese language at the border of Serang Regency, Banten Province. The research problem formulation in this research was the external innovation and categories found in the usage of the Banten dialect of Javanese language at the border of Serang Regency, Banten Province. This research used a qualitative descriptive of observation method with the techniques of engaging in conversation and contact or mutual conversation with the technique of simultaneous conversation. This technique was then followed by note-taking, both from the interlocutors and language assistants. The research was conducted in eight villages in the districts of Pamarayan, Pontang, Tanara, and Anyer. The sample informants in each village consisted of 2 native speakers of the Banten dialect of Javanese language. The research instrument used for interviewing was a list of 314 questions. The findings of this research indicate that each region exhibited symptoms of external innovation, namely the loanwords from the contact with other language at the border of Serang Regency, such as the loanwords of Sundanese, Javanese, Betawi, and Lampung vocabulary. Variant categories of word classes are also found, such as nouns, adjectives, verbs, directional words, conjunctions, agreement words, and question words. Suggestions that could be considered in this research include creating an etymology dictionary or a dialect dictionary. Those two dictionaries are considered necessary because currently, the influence of other language might lead to convergence, and therefore documentation is needed for further study or the preservation of the language in the future